2009
DOI: 10.4049/jimmunol.0901366
|View full text |Cite
|
Sign up to set email alerts
|

Smallpox Inhibitor of Complement Enzymes (SPICE): Dissecting Functional Sites and Abrogating Activity

Abstract: Although smallpox was eradicated as a global illness more than 30 years ago, variola virus and other related pathogenic poxviruses, such as monkeypox, remain potential bioterrorist weapons or could re-emerge as natural infections. Poxviruses express virulence factors that down-modulate the host’s immune system. We previously compared functional profiles of the poxviral complement inhibitors of smallpox, vaccinia, and monkeypox known as SPICE, VCP (or VICE), and MOPICE, respectively. SPICE was the most potent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 70 publications
(159 reference statements)
1
30
0
Order By: Relevance
“…Later, we examined the contribution of each of the variant amino acids of SPICE and demonstrated that substitution of four SPICE residues (H98Y/S103Y/E108K/E120K) in VCP is enough to formulate VCP as potent as SPICE in inactivating human C3b as well as C4b (15). The functional advantage provided by K120 in SPICE was also demonstrated by Liszewski et al (16).…”
mentioning
confidence: 82%
“…Later, we examined the contribution of each of the variant amino acids of SPICE and demonstrated that substitution of four SPICE residues (H98Y/S103Y/E108K/E120K) in VCP is enough to formulate VCP as potent as SPICE in inactivating human C3b as well as C4b (15). The functional advantage provided by K120 in SPICE was also demonstrated by Liszewski et al (16).…”
mentioning
confidence: 82%
“…HS1, HS2, and HS3 (indicated in red) denote the three heparin binding sites identified earlier (53). Residues forming these sites also play a role in complement regulation (53). HS1, heparin binding site 1; HS2, heparin binding site 2; HS3, heparin binding site 3. domain 1 in VCP participates in dissociation of C2a (Fig.…”
Section: Vcp Domains Critical For Daasmentioning
confidence: 99%
“…Identification of domains important for various activities, except for C3b and C4b binding (34) and heparin binding (34), is based on data presented in this study. HS1, HS2, and HS3 (indicated in red) denote the three heparin binding sites identified earlier (53). Residues forming these sites also play a role in complement regulation (53).…”
Section: Vcp Domains Critical For Daasmentioning
confidence: 99%
“…Further investigation of these and other virulence factors will provide insight into pathogenesis and may provide potential strategies for therapeutic intervention. 69 Many aspects of smallpox remain a mystery, and further research on the disease and on countermeasures is needed. Because it is not possible to study naturally occurring smallpox and because experimental VARV infection of humans is ethically and morally prohibited, the US Food and Drug Administration established the animal efficacy rule, or ''animal rule.''…”
Section: Smallpox In Humansmentioning
confidence: 99%